2013
DOI: 10.33899/rjs.2013.77814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin vs. Glibenclamide on Serum Leptin Concentration in Type 2 Diabetic Patients

Abstract: This study was done to assess the effects of metformin and glibenclamide on serum leptin concentration in type 2 diabetic patients. The study involved 137 patients suffering from type 2 diabetes mellitus. They were divided into 3 groups. The first group involves 35 newly diagnosed diabetic patients, who did not take any hypoglycemic agents. The second group involves 52 patients on metformin monotherapy, whereas the third group involves 50 patients on glibenclamide monotherapy. Another group which involved 35 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Likewise, metformin mitigated hyperuricemia [97], restored leptin sensitivity, and reduced serum leptin concentrations in overweight diabetic patients [98]. Metformin could also increase adiponectin expression and boost its secretion from the subcutaneous adipose tissue [99].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, metformin mitigated hyperuricemia [97], restored leptin sensitivity, and reduced serum leptin concentrations in overweight diabetic patients [98]. Metformin could also increase adiponectin expression and boost its secretion from the subcutaneous adipose tissue [99].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have found that metformin has particular influences at the level of the hypothalamic centers which are responsible for satiety and hunger, leading to a reduction in food intake in both diabetic and non-diabetic patients [13]. According to existing evidence, the weight loss property of this medication may be influenced by increased leptin sensitivity [12].…”
mentioning
confidence: 99%